2010
DOI: 10.1093/cvr/cvq118
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the pathophysiological relevance of TRPA1 receptors in the cardiovascular system in vivo

Abstract: TRPA1 is involved in mediating vasodilation. TRPA1 can also influence changes in blood pressure of possible relevance to autonomic system reflexes and potentially to vasovagal/neurocardiogenic syncope disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
128
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(133 citation statements)
references
References 38 publications
4
128
0
1
Order By: Relevance
“…Finally, we investigated whether 4-ONE can, like the exogenous agonists mustard oil and cinnamaldehyde (Pozsgai et al, 2010), influence peripheral blood flow in vivo. We have shown previously that activation of TRPV1 by capsaicin triggers neurogenic vasodilatation in the mouse in vivo (Grant et al, 2002;Starr et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, we investigated whether 4-ONE can, like the exogenous agonists mustard oil and cinnamaldehyde (Pozsgai et al, 2010), influence peripheral blood flow in vivo. We have shown previously that activation of TRPV1 by capsaicin triggers neurogenic vasodilatation in the mouse in vivo (Grant et al, 2002;Starr et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of 10 nmol 4-ONE on hind paw blood flow was investigated. Previous studies have shown that topical application of mustard oil induces a potent TRPA1-dependent vasodilatation (Pozsgai et al, 2010), but 4-ONE is not absorbed into the skin via topical application. Here, intraplantar injections of 50 l of 4-ONE or vehicle were given into either hind paw, and plantar blood flow was measured for 30 min.…”
Section: -One Induces Dose-and Time-dependent Mechanical Hyperalgesimentioning
confidence: 97%
See 1 more Smart Citation
“…TRPV1 channels have also been proposed to be involved in the pathogenesis of salt-induced hypertension. TRPV1 expression in mesenteric resistance arteries, the renal cortex and medulla, CGRP levels in dorsal root ganglia, and CGRP-positive sensory nerve density in mesenteric resistance arteries were significantly up-regulated during [57,58] TRPP2 VSMC Contributes to the myogenic response of resistance-size cerebral arteries [47] high-salt intake in Dahl salt-resistant rats, which acted to prevent salt-induced increases in blood pressure [72]. In contrast, TRPV1 expression and function was impaired in Dahl salt-sensitive rats, which rendered Dahl salt-sensitive rats to salt load in terms of blood pressure regulation [72].…”
Section: Trp Channel Subtypes M and V Have Antihypertensive Effectsmentioning
confidence: 97%
“…In a previous study, we demonstrated that TRPM8 activation, by its agonist menthol, antagonized vasoconstriction by inhibiting Ca 2+ signaling-mediated RhoA/ROCK activation in the vasculature [56]. TRPA1 channels are present in the endothelium and mediated vasodilatation via endothelium-dependent and independent mechanisms [57,58]. The role of TRPA1 in the cardiovascular system remains elusive (Table 1).…”
Section: Trp Channels Contribute To Vasodilatationmentioning
confidence: 99%